2020
DOI: 10.1093/molbev/msaa029
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Shifts from Cis- to Trans-splicing of Gymnosperm Mitochondrial Introns

Abstract: Hundreds of plant mitogenomes have been sequenced from angiosperms, but relatively few mitogenomes are available from its sister lineage, gymnosperms. To examine mitogenomic diversity among extant gymnosperms, we generated draft mitogenomes from 11 diverse species and compared them with four previously published mitogenomes. Examined mitogenomes from Pinaceae and cycads retained all 41 protein genes and 26 introns present in the common ancestor of seed plants, whereas gnetophyte and cupressophyte mitogenomes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 47 publications
8
46
1
Order By: Relevance
“…Other NADH-ubiquinone oxidoreductase genes (specifically nad1, nad2, and nad5) typically contain trans-splicing introns (Chapdelaine and Bonen 1991;Knoop, et al 1991;Binder, et al 1992), but this is not the case for nad7 in most angiosperm mitogenomes. Such transitions from cis-to trans-splicing are relatively common in plant mitochondria (Qiu and Palmer 2004), and it was recently shown that the Pinaceae has independently evolved transsplicing of this same nad7 intron (Guo, et al 2020).…”
Section: Agrostemma Githago and Silene Chalcedonicamentioning
confidence: 99%
“…Other NADH-ubiquinone oxidoreductase genes (specifically nad1, nad2, and nad5) typically contain trans-splicing introns (Chapdelaine and Bonen 1991;Knoop, et al 1991;Binder, et al 1992), but this is not the case for nad7 in most angiosperm mitogenomes. Such transitions from cis-to trans-splicing are relatively common in plant mitochondria (Qiu and Palmer 2004), and it was recently shown that the Pinaceae has independently evolved transsplicing of this same nad7 intron (Guo, et al 2020).…”
Section: Agrostemma Githago and Silene Chalcedonicamentioning
confidence: 99%
“…2016 ). This year saw a number of mitochondrial genomes published in short succession ( Guo et al. 2020 ; Kan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Also, trans -spliced genes are common in mitochondrial genomes ( Kamikawa et al. 2016 ; Guo et al. 2020 ), and no purpose-built software tool exists for identifying and annotating trans -spliced genes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies on intra-specific mitogenome variation demonstrated that a genome rearrangement or a frequency shift between different mitotypes in an individual could occur in a short time [30][31][32]. This extreme genome rearrangement can affect a gene order and shift the splicing mode (from cis to trans) of introns [33]. In angiosperms, it was estimated that the shift in one of the introns of the nad1 gene (nad1i728), which contains the matR gene within it, occurred at least 15 times [34].…”
Section: Introductionmentioning
confidence: 99%